PEMBERIAN PAKAN IKAN RUCAH DENGAN DOSIS YANG BERBEDA TERHADAP PERFORMA PERTUMBUHAN LOBSTER PASIR (Panulirus homarus) - Made Doddy Nugraha Doddy; Dewi Nur’aeni Setyowati; Saptono Waspodo (Jurnal Perikanan Unram, 2019)
One type of lobster that is widely known and developed by the people of Indonesia, especially in West Nusa Tenggara is sand lobster (Panulirus homarus) because the prospect of cultivating sand lobster promising in terms of economy and natural conditions in the West Nusa Tenggara region in meeting the market demand and maintaining the balance of production. In several studies that have been done previously there is no further research regarding the optimal feed dose for lobster. Inadequate feeding will trigger cannibalism in lobsters and excessive feeding will make the feed wasted and can cause biofoling in the culture container. The purpose of this research is to find out the best dose of trash fish feed given to the growth performance of sand lobster. This study used a group randomized design with 3 treatments, namely at a dose of 4%, 5%, and 6%, each treatment was repeated 3 times to obtain 9 experimental units. The results of analysis of variance with 5% significance level showed that feeding trash fish with different doses have a real effect on the survival of sand lobsters (Panulirus homarus).